2021
DOI: 10.1126/scitranslmed.aay1050
|View full text |Cite
|
Sign up to set email alerts
|

Na v 1.7 target modulation and efficacy can be measured in nonhuman primate assays

Abstract: Humans with loss-of-function mutations in the Nav1.7 channel gene (SCN9A) show profound insensitivity to pain, whereas those with gain-of-function mutations can have inherited pain syndromes. Therefore, inhibition of the Nav1.7 channel with a small molecule has been considered a promising approach for the treatment of various human pain conditions. To date, clinical studies conducted using selective Nav1.7 inhibitors have not provided analgesic efficacy sufficient to warrant further investment. Clinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…Our finding that many nociceptors depend on Na v 1.7 for propagation is consistent with that of a report in Na v 1.7 KO mice 18 and a pharmacological study in nonhuman primates. 28 However, these findings seem to contradict an in vivo imaging study that suggested peripheral excitability of nociceptors in Na v 1.7 KO mice was largely unaffected by the loss of channel function. 30 Using pharmacological tools to assess protein function in neurons permits a "before and after" comparison, whereas a KO approach only allows for this when sampling from a global population.…”
Section: Discussionmentioning
confidence: 93%
“…Our finding that many nociceptors depend on Na v 1.7 for propagation is consistent with that of a report in Na v 1.7 KO mice 18 and a pharmacological study in nonhuman primates. 28 However, these findings seem to contradict an in vivo imaging study that suggested peripheral excitability of nociceptors in Na v 1.7 KO mice was largely unaffected by the loss of channel function. 30 Using pharmacological tools to assess protein function in neurons permits a "before and after" comparison, whereas a KO approach only allows for this when sampling from a global population.…”
Section: Discussionmentioning
confidence: 93%
“…Poor design of trials [for example, failure to recognize that heterogeneity of sensory phenotypes of patients may hint at different underlying mechanisms ( 65 , 66 ) or lack of target modulation assays to enable clinical interpretation of NaV1.7 inhibitors, but see ( 67 )] has likely led to faltering of NaV1.7-targeted drugs at the doorstep of the clinical stage ( 68 ). Future clinical trials for CRMP2 SUMOylation inhibitors should stratify patients with chronic pain based on the presence of SUMOylated CRMP2 in skin biopsies; increased amount of SUMOylated CRMP2 are present in the skin, spinal cord, and sciatic nerves in preclinical models of neuropathic pain ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo antinociceptive potency of MK-2075 was determined preclinically in the rhesus thermode heat withdrawal study based on treatment-mediated decrease in magnitude of behavioral response to a thermal stimulus on the forearm. Rhesus thermode heat withdrawal was measured by brief application of heat delivered to the forearm of rhesus macaque as described by Vardigan et al (2018) and Kraus et al (2021). Briefly, four test temperatures: 44 °C, 46 °C, 48 °C, and 50 °C were delivered randomly and repeated six times per session.…”
Section: Rhesus Thermode Heat Withdrawal Methods and Modeling Strategymentioning
confidence: 99%
“…Humans with genetic mutations leading to a loss of function (LOF) of the NaV1.7 channel have a congenital indifference to pain and anosmia while a gain of function mutations can result in pain syndromes such as primary erythromelalgia (Dib-Hajj et al, 2007;Weiss et al, 2011). Pharmacological inhibition of NaV1.7 channels in nonhuman primates has demonstrated a similar phenotype to humans with a genetic loss of NaV1.7 function, including hyposmia and analgesia (Kraus et al, 2021). While drugs with sodium channel-blocking activity such as carbamazepine have demonstrated some utility in pain treatment, their nonselective nature contributes to dose-limiting adverse effects (Tanelian and Victory, 1995;Dick et al, 2007;Moulin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%